Steroid profiling using liquid chromatography mass spectrometry during adrenal vein sampling in patients with primary bilateral macronodular adrenocortical hyperplasia - Zhang, Ru; Rubinstein, German; Vetrivel, Sharmilee; Kunz, Sonja; Vogel, Frederick; Bouys, Lucas; Bertherat, Jérôme; Kroiss, Matthias; Deniz, Sinan; Osswald, Andrea; Knösel, Thomas; Bidlingmaier, Martin; et al. (Frontiers in Endocrinology, 2022)
Adrenal vein sampling (AVS) is not a routine procedure in patients with primary bilateral macronodular adrenocortical hyperplasia (PBMAH), but has been used to determine lateralization of cortisol secretion in order to guide decision of unilateral adrenalectomy. Our aim was to characterize the steroid fingerprints in AVS samples of patients with PBMAH and hypercortisolism and to identify a reference hormone for AVS interpretation. Retrospectively, we included 17 patients with PBMAH from the German Cushing’s registry who underwent AVS. 15 steroids were quantified in AVS and peripheral blood samples using LC-MS/MS. We calculated lateralization indices and conversion ratios indicative of steroidogenic enzyme activity to elucidate differences between individual adrenal steroidomes and in steroidogenic pathways. Adrenal volume was negatively correlated with peripheral cortisone (r=0.62, p<0.05). 24-hour urinary free cortisol correlated positively with peripheral androgens (rDHEA=0.57, rDHEAS=0.82, rA=0.73, rT=0.54, p<0.05). DHEA was found to be a powerful reference hormone with high selectivity index, which did not correlate with serume cortisol and has a short half-life. All investigated steroids showed lateralization in single patients indicating the heterogenous steroid secretion pattern in patients with PBMAH. The ratios of corticosterone/aldosterone (catalyzed by CYP11B2), androstenedione/dehydroepiandrosterone (catalyzed by HSD3B2) and cortisone/cortisol (catalyzed by HSD11B2) in adrenal vein samples were higher in smaller adrenals (p<0.05). ARMC5 mutation carriers (n=6) showed lower androstenedione/17-hydroxyprogesterone and higher testosterone/androstenedione (p<0.05) ratios in peripheral blood, in line with lower peripheral androstenedione concentrations (p<0.05). Steroid profiling by LC-MS/MS led us to select DHEA as a candidate reference hormone for cortisol secretion. Lateralization and different steroid ratios showed that each steroid and all three steroidogenic pathways may be affected in PBMAH patients. In patients with germline ARMC5 mutations, the androgen pathway was particularly dysregulated.